El diseño curricular como factor de calidad educativa en el área de matemática (2021)
The purpose of this research was to design a proposal to improve the process of teaching mathematics in junior high school based on academic management for curriculum design in this area. It was structured with a qualitative-descriptive approach, an interpretative paradigm, a nonexperimental design and a non-random and intentional sample. A semi-structured interview of ten questions was applied to 17 teachers in the rural area of the department of Magdalena, obtaining as a result the importance of the BLR and that the evaluations, recommendations and participation of the students should be taken into account in terms of methodology and fundamental orientations within the teaching-learning process based on the schemes to be dealt with during the school year, contextualizing it with their environment. It is concluded that the most relevant BLR will be those that result from a previous evaluation and in which the existing deficiencies will be emphasized and transversal mathematics projects are carried out with other areas of knowledge taking into account the BLR, where only the realization of projects in problem solving is specified., which of course has to do with reading comprehension and the development of thinking skills.